2020
DOI: 10.21203/rs.3.rs-90645/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microscale diffusiophoresis of proteins

Abstract: Living systems are characterised by their spatially highly inhomogeneous nature which is susceptible to modify fundamentally the behaviour of biomolecular species, including the proteins that underpin biological functionality in cells. Spatial gradients in chemical potential are known to lead to strong transport effects for colloidal particles, but their effect on molecular scale species such as proteins has remained largely unexplored. Here we demonstrate with microfluidic measurements that individual protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The authors provided an estimation of the zeta potential and mentioned potential microfluidic application using MgCl 2 . One-dimensional diffusiophoresis of bovine serum albumin (BSA), β-lactoglobulin, myoglobin, and lysozyme under gradient of LiCl, KCl, and KIO 2 are also demonstrated by Peter et al using a dead-end pore geometry (Figure ).…”
Section: Particles Used In Experimental Studiesmentioning
confidence: 79%
See 3 more Smart Citations
“…The authors provided an estimation of the zeta potential and mentioned potential microfluidic application using MgCl 2 . One-dimensional diffusiophoresis of bovine serum albumin (BSA), β-lactoglobulin, myoglobin, and lysozyme under gradient of LiCl, KCl, and KIO 2 are also demonstrated by Peter et al using a dead-end pore geometry (Figure ).…”
Section: Particles Used In Experimental Studiesmentioning
confidence: 79%
“…A microfluidic approach for diffusiophoresis of macromolecules is demonstrated by Palacci et al for DNA focusing, , and later more groups visualized and studied diffusiophoresis of lipid vesicles, DNA, proteins, and other macromolecules. ,,, , In the studies by Palacci et al, , under a concentration gradient of LiCl set up across the flow, colloidal particles and λ-DNA showed transient diffusiophoretic focusing. The measurements and calculations for the peak propagation indicated that fluorescent-tagged λ-DNA behaves similarly to the polystyrene particles (carboxylate-modified PS; d = 200 nm).…”
Section: Particles Used In Experimental Studiesmentioning
confidence: 99%
See 2 more Smart Citations